2006
DOI: 10.1093/jat/30.6.353
|View full text |Cite
|
Sign up to set email alerts
|

Disposition of Hydrocodone in Hair

Abstract: The use of prescription drugs, including synthetic opiates, is increasing in the U.S., with emergency room reports showing a dramatic rise in prescription opiate abuse. As part of an ongoing study, the hair of admitted opiate users was analyzed for hydrocodone and hydromorphone, as well as codeine, morphine, and 6-acetylmorphine in order to determine if there was any correlation between self-reported frequency of opiate intake and the concentration of drug detected in hair. The hairs were confirmed using gas c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…Of the nine samples tested for pain management drugs, one sample screened positively for carisoprodol (9200 pg/mg); four tested positively for methadone (two had insufficient sample remaining to confirm, two had concentrations of 1235 and 2389 pg/mg); five samples were positive for opiates, which were confirmed using previously published methods at concentrations of codeine (72 pg/mg); oxycodone 10,175 and 707 pg/mg; and hydrocodone at 882 pg/mg [3]. One sample had insufficient sample remaining for analysis.…”
Section: Forensic Samplessupporting
confidence: 60%
See 1 more Smart Citation
“…Of the nine samples tested for pain management drugs, one sample screened positively for carisoprodol (9200 pg/mg); four tested positively for methadone (two had insufficient sample remaining to confirm, two had concentrations of 1235 and 2389 pg/mg); five samples were positive for opiates, which were confirmed using previously published methods at concentrations of codeine (72 pg/mg); oxycodone 10,175 and 707 pg/mg; and hydrocodone at 882 pg/mg [3]. One sample had insufficient sample remaining for analysis.…”
Section: Forensic Samplessupporting
confidence: 60%
“…Hadidi et al reported a case of the detection of tramadol in hair [1], while others have reported on the determination of oxycodone, hydrocodone, methadone and benzodiazepines [2][3][4][5]. Fentanyl is a synthetic opioid with similar properties to morphine yet up to 200 times more potent.…”
Section: Introductionmentioning
confidence: 99%
“…Day et al reached a detection limit of 10 pg/ml for THC-COOH in oral fluid by GC/MS/MS [174]. Moore et al developed a GC/MS method using a micro-fluidic Dean's switch for two-dimensional (2D) chromatography to sufficiently improve signal to noise, allowing the monitoring of THC-COOH concentrations of ≥ 2 pg/ml in oral fluid [175]. Extraction efficiency for THC-COOH from the Quantisal™ (Immunalysis, Pomona, CA) oral-fluid collection device was 80% at a concentration of 10 pg/ml, with a coefficient of variation of 8.23%.…”
Section: Oral-fluid Testingmentioning
confidence: 99%
“…One of the major challenges for oral fluid analysis is the generally small specimen size and consistent collection [89], which limits the ability to perform multidrug testing and especially limits the definitive identification of drugs following positive screening tests. This is often compounded by the mouth dryness that accompanies use of many drugs including opioids [90].…”
Section: Sample Adulteration and Alternative Matrix Testingmentioning
confidence: 99%